(untitled) (Agrikan Jurnal Agribisnis Perikanan, 2022)
HABs is a term that describes the species of harmful phytoplankton found in the waters. One of the factors triggering its development is the increase in the concentration of nutrient types nitrogen (N) and Posfor (P) is very high. To that end, a study aimed at detecting potentially dangerous types of phytoplankton (HABs) in a water has been conducted in May-July 2021. The waters in question are the coastal waters of the southern part of Makassar (JB) and the coastal waters of Takalar (coastal waters beba = BB, Boddia = BG, and Sanrobone = SB). The waters are waters located on the western coast of the southern part of South Sulawesi. Enumeration of HABs is performed on samples of water that has been filtered using net plankton. The results showed that as many as 10 potential genera of HABs have been found. The genera in question are Bacteriastrum, Chaetoceros, Nitzschia, and Pseudo-nitzchia of the Bacillariophyceae group, and Ceratium, Dinophysis, Gymnodinium, Peridinium, Prorocentrum, and Protoperidinium of the Dynophycea group. From the results of the proportion test, potentially HABs were found to be lower at about 30.13% when compared to the non-HABs phytoplankton group of about 69.87% based on spatial, and 30.57% versus 69.43% based on temporal.